Multiple osteochondromatosis (EXT1-EXT2-CDG): clinical, biochemical, and molecular studies in a cohort of 33 Latin American patients - Delgado, María Andrea (2013)
Fil: Delgado, María Andrea. Universidad Nacional de Córdoba. Facultad de Odontología. Cátedra Química Biológica"A"; Argentina.